2011
DOI: 10.1002/lt.22280
|View full text |Cite
|
Sign up to set email alerts
|

Splenic artery embolization for the treatment of refractory ascites after liver transplantation

Abstract: Refractory ascites (RA) is a challenging complication after orthotopic liver transplantation. Its treatment consists of the removal of the precipitating factors. When the etiology is unknown, supportive treatment can be attempted. In severe cases, transjugular intrahepatic portosystemic shunts, portocaval shunts, and liver retransplantation have been used with marginal results. Recently, splenic artery embolization (SAE) has been described as an effective procedure for reducing portal hyperperfusion in patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
61
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 43 publications
(65 citation statements)
references
References 31 publications
3
61
0
1
Order By: Relevance
“…Clearly, the authors and their colleagues in interventional radiology have developed significant expertise in optimizing the intrahepatic hemodynamics after orthotopic liver transplantation and are facile with spleen-preserving proximal splenic artery embolization (SAE). 2,3 The authors also reinforce the evidence supporting 2 risk factors for PHP: the spleen volume and the spleen/liver volume ratio.Although the current study is an important starting point for discussion, it suffers from some design flaws that make the data difficult to extrapolate for use by a wider audience. A lack of randomization and the absence of standardized indications for SAE limit the generalizability of the data.…”
supporting
confidence: 60%
“…Clearly, the authors and their colleagues in interventional radiology have developed significant expertise in optimizing the intrahepatic hemodynamics after orthotopic liver transplantation and are facile with spleen-preserving proximal splenic artery embolization (SAE). 2,3 The authors also reinforce the evidence supporting 2 risk factors for PHP: the spleen volume and the spleen/liver volume ratio.Although the current study is an important starting point for discussion, it suffers from some design flaws that make the data difficult to extrapolate for use by a wider audience. A lack of randomization and the absence of standardized indications for SAE limit the generalizability of the data.…”
supporting
confidence: 60%
“…(Evidence level C) Comment: Although PSE and splenectomy increase platelet and leukocyte counts, PSE allows preservation of adequate splenic tissue to safeguard against overwhelming infection [221]. Beneficial effects of PSE on refractory ascites after liver transplant were reported [222,223]. PSE reduced prothrombin time and increased serum albumin levels at 12 months [224].…”
Section: Portal Vein Thrombosismentioning
confidence: 99%
“…Endovascular treatment options also play a limited role in nonvascular causes, such as recurrent infection or rejection needing medical treatment or liver transplant. 1,4,5 …”
Section: Diagnosis and Treatment Of Refractory Ascitesmentioning
confidence: 99%
“…33,31 Published reports on the use of splenic artery embolization in the treatment of RA after liver transplant are scarce. In the setting of liver transplant, Chang and associates, 34 Quintini and associates, 5 and Kim and associates 35 showed that splenic artery embolization was safe and effective in reducing the portal vein velocity immediately, translating into resolution of ascites in most of the patients. In contrast to distal embolization, a proximal embolization technique allows decreased splenic flow to produce the desired amount of ischemia while allowing distal revascularization, thereby preventing significant splenic infarct and complications.…”
Section: Transjugular Intrahepatic Portosystemic Shuntmentioning
confidence: 99%
See 1 more Smart Citation